The Role of Dhikr-Based Mindfulness in Reducing Test Anxiety among Senior High School Students in Indonesia - Furkon, Muhammad; Latuny, Leny Sopia; Manoppo, Yance; Sutarum, Sutarum (Yayasan Minang Darussalam, 2025)
This study explores the role of dhikr-based mindfulness in reducing test anxiety among senior high school students in Indonesia. Test anxiety has been identified as a significant psychological barrier that negatively affects students’ academic performance and emotional well-being. Drawing on the integration of Islamic spiritual practice and contemporary mindfulness techniques, this research investigates whether dhikr—repetitive remembrance of Allah—can serve as an effective intervention to regulate emotions and enhance focus during academic evaluations. Using a quasi-experimental design, senior high school students were divided into an experimental group receiving dhikr-based mindfulness training and a control group following regular study routines. Data were collected through standardized test anxiety scales and analyzed with both descriptive and inferential statistics. The findings indicate a significant reduction in test anxiety levels among the experimental group, suggesting that dhikr-based mindfulness fosters relaxation, spiritual awareness, and self-regulation. This research highlights the potential of combining religious practices with psychological interventions to support students’ mental health in Islamic educational settings. Furthermore, it offers implications for educators, counselors, and policymakers in designing holistic programs that integrate spirituality with evidence-based approaches to improve students’ academic resilience.